2013
DOI: 10.1002/grl.50732
|View full text |Cite
|
Sign up to set email alerts
|

Using core complex geometry to constrain fault strength

Abstract: [1] We present the first model results showing that some core complex detachment faults are strong and that their strength has to be in a narrow range to allow certain extensional structures to develop. The structures we simulate are kilometer-scale "rider blocks" that are particularly well observed on some oceanic core complexes as well as continental metamorphic core complexes. Previous numerical simulations of lithospheric extension produced the large-offset, core complex-forming, normal faults only when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 53 publications
5
56
0
Order By: Relevance
“…Our models thus begin with the assumption that faults have Byerlee friction (coefficient of friction ≅ 0.6) but then weaken with continued slip. This strength evolution is used to simulate normal faults in previous efforts [e.g., Lavier and Manatschal , ; Huismans and Beaumont , ], and our additional tests (supporting information Figure S2) suggest that decreasing the fault weakening effect does not change our overall results (but see Choi et al [], for examples of how changing fault weakening can change crustal fault structure).…”
Section: Methodsmentioning
confidence: 99%
“…Our models thus begin with the assumption that faults have Byerlee friction (coefficient of friction ≅ 0.6) but then weaken with continued slip. This strength evolution is used to simulate normal faults in previous efforts [e.g., Lavier and Manatschal , ; Huismans and Beaumont , ], and our additional tests (supporting information Figure S2) suggest that decreasing the fault weakening effect does not change our overall results (but see Choi et al [], for examples of how changing fault weakening can change crustal fault structure).…”
Section: Methodsmentioning
confidence: 99%
“…It has been used to simulate faults in a variety of problems (e.g. Buck et al, 2005;Choi et al, 2013;Hassani and Chéry, 1996;Lavier et al, 2000;Poliakov and Buck, 1998). To recap the main features, geoFLAC has Newton's second law in its dynamic form as the governing equation.…”
Section: Geoflacmentioning
confidence: 99%
“…They also suggested that the lack of synextensional clastic or volcanic infill above the fault could preclude rider block formation. Highresolution numerical simulations done by Choi et al (2013) confirmed the Reston and Ranero (2011) suggestions but went on to show that the formation of large-offset normal faults with rider blocks puts tight constraints on the strength of these faults. Highresolution numerical simulations done by Choi et al (2013) confirmed the Reston and Ranero (2011) suggestions but went on to show that the formation of large-offset normal faults with rider blocks puts tight constraints on the strength of these faults.…”
Section: 'Riders Blocks' and Constraints On Fault Strengthmentioning
confidence: 83%
“…Highresolution numerical simulations done by Choi et al (2013) confirmed the Reston and Ranero (2011) suggestions but went on to show that the formation of large-offset normal faults with rider blocks puts tight constraints on the strength of these faults. Also, Choi et al (2013) showed that rider blocks develop when the dominant form of weakening is by reduction of fault cohesion, while faults that weaken primarily by friction reduction do not form distinct rider blocks. A narrow range of fault weakening, relative to intact surrounding rock, allows for a consecutive series of rider blocks to emerge in a core complex-like geometry ( Figure 24).…”
Section: 'Riders Blocks' and Constraints On Fault Strengthmentioning
confidence: 83%
See 1 more Smart Citation